2001
DOI: 10.1111/j.1349-7006.2001.tb01144.x
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Osteosarcoma Cell Line with a Potential to Develop Ossification upon Transplantation

Abstract: An osteosarcoma cell line has been established from a soft tissue tumor that occurred spontaneously in a BALB/c mouse. This cell line showed ossification when transplanted into syngeneic mice. To examine the mechanism of bone formation, the expression of mRNAs for osteoblastic and chondroblastic markers and factors associated with ossification has been investigated. In culture, the cells exhibited a spindle shape in the growth phase, but had a polygonal shape in the stationary phase. Reverse transcription-poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…OPN is unlikely associated with hard tissue formation of the salivary gland tumors. On the other hand, OPN is frequently expressed in osteosarcoma (23). Total absence of OPN expression may support the salivary gland origin of the present case.…”
Section: Discussionsupporting
confidence: 72%
“…OPN is unlikely associated with hard tissue formation of the salivary gland tumors. On the other hand, OPN is frequently expressed in osteosarcoma (23). Total absence of OPN expression may support the salivary gland origin of the present case.…”
Section: Discussionsupporting
confidence: 72%
“…Osteosarcoma cell lines have been established from human, dog and rat, and these cell lines have the ability to undergo ossification after xenotransplantation [13,16,21,29,31]. Thus the cell lines are useful for studies of the mechanism of ossification as well as the relationship between BMPs and metastasis of osteosarcoma.…”
mentioning
confidence: 99%
“…In fact, in most OS, there are also chondrocytes and fibroblasts that present in the matrix. It has been reported that there is cartilage matrix in the tumor tissues of mice transplanted with OS cell lines, and it has ossification similar to the process of endochondral ossification, suggesting that chondrogenesis or endochondral ossification plays a role in the development of OS [19,20]. RUNX2 is a transcription factor belonging to the Runt domain gene family, which is to play a crucial role in osteoblast differentiation and chondrocyte maturation [39,114,115].…”
Section: Chemical Induction Modelsmentioning
confidence: 99%
“…Chondrocytes and fibroblasts are also present in the tumor stroma of many osteosarcomas. In addition, in the induced mouse OS model, cartilage matrix was found present in the tumor tissue and ossification occurred through similar process of endochondral ossification [19,20]. As a transcription factor, RUNX2 is known to play a crucial role in osteoblast differentiation and chondrocyte hypertrophy or maturation.…”
Section: Introductionmentioning
confidence: 99%